2018
DOI: 10.1051/meca/2018049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of couple-stresses and piezo-viscous effects in a layered connecting-rod bearing

Abstract: In this work, the combined effects of couple-stresses and piezo-viscosity on the dynamic behavior of a compression ignition engine big-end connecting-rod bearing with elastic layer are investigated using the V. K. Stokes micro-continuum theory. It is assumed that the journal (crankpin) is rigid and the big-end bearing consists of a thin compressible elastic liner fixed in an infinitely stiff housing. The governing Reynolds' equation and the viscous dissipation term appearing on the RHS of energy equation are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Over the last few years, in the literature, there have been a number of investigations reported on non-Newtonian (shear-thinning and piezoviscous) lubricants, however, they are mainly limited to circular journal bearings. 1018 Sinhasan and Sah 10 numerically investigated the static as well as the dynamic behavior of hydrostatic journal bearing by using the Finite Element Method. Further, they evaluated the performance characteristics of bearings lubricated with non-Newtonian lubricants using the cubic shear stress law model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, in the literature, there have been a number of investigations reported on non-Newtonian (shear-thinning and piezoviscous) lubricants, however, they are mainly limited to circular journal bearings. 1018 Sinhasan and Sah 10 numerically investigated the static as well as the dynamic behavior of hydrostatic journal bearing by using the Finite Element Method. Further, they evaluated the performance characteristics of bearings lubricated with non-Newtonian lubricants using the cubic shear stress law model.…”
Section: Introductionmentioning
confidence: 99%
“…At higher eccentricity ratios, the power-law model's visco-metric exponent has a significant effect. Using the Stokes micro-continuum theory, Laouadi et al 14 investigated the interactive behavior of piezo-viscous effects and couple stress on the performance of a multilayer connecting rod bearing. It was reported that couple stress and piezovicous effects significantly influence the dynamic behavior of dynamically loaded bearings.…”
Section: Introductionmentioning
confidence: 99%
“…The combined effects of couple-stresses and piezo-viscosity on the dynamic behavior of a compression ignition engine big-end connecting-rod bearing with elastic layer are investigated using the V. K. Stokes micro-continuum theory were presented by Laouadi et all. 18…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the viscous compression effect needs to be taken into account when the local pressure approaches 200 MPa and the shear thinning effect cannot be neglected when the shear rate reaches 106 1/s [20]. Bouzid et al considered the combined effect of coupling stress and viscous compression effect on the dynamic characteristics of connecting rods in their study of connecting rod sliding bearings and found that the coupling stress and viscous compression effect have a significant effect on the nonlinear dynamic behavior of dynamically loaded bearings [21]. Parinam considered the shear thinning effect in the study of line contact sliding friction [22].…”
Section: Introductionmentioning
confidence: 99%